Effects of the Participative Management Model on Effectiveness for Nursing Services of One-Day Surgery Patieats and Professional Nurses’ Satisfaction - Machima, Nantawan; Prachusilpa, Gunyadar; Apituknapanond, Panta (Journal of health and health management, 2023)
The purposes of this Quasi experimental research were to compare the effectiveness of the revised one-day surgery nursing model with the previous method and to study the satisfaction of Samutpakarn hospital’s professional nurses. The population was 30 professional nurses by purposive sampling technique. The research instrument were the one-day surgery model, one-day surgery nursing activities handbook, one-day surgery’s preparation instruction sheet for Hernia’s patient, incident form and professional nurses’ satisfaction questionnaires which all were validated and approved by professional experts. The Cronbach’s alpha coefficient for professional nurses’ satisfaction questionnaires was .951. Data were analyzed by using frequency, percentage, mean standard deviation and dependent t-test. The results revealed that the revised one-day surgery nursing model, the number of the incidence rate of postponing-cancelling surgeries and post-operative complication occurred from the previous model was able to reduce to zero and enhanced the satisfactory level of professional nurses. ( = 3.96, SD = .565) and affected to professional nurses’ satisfaction with statistical significance at .05